Penentuan Jumlah Karakter pada Plat Nomor Kendaraan dengan menggunakan Selective Ratio Bounding Box - Juniman Arief; Fitri Utaminingrum; Yuita Arum Sari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The system of determining the number of characters on the vehicle number plate is one of the applications required in modern times today. The first step taken is image capture using the camera, then perform image processing and segmentation on the vehicle license plate image. Then do the determination of the number of characters on the vehicle number plate by using bounding box and selective ratio bounding box. Before the process of detection or the introduction of vehicle license plate required the validity to determine the number of characters on the license plate of the vehicle in order to know the number of characters on the license plate of the vehicle so as not to be wrong in recognizing the character on the license plate of the vehicle. It is expected that the application is able to determine the number of characters on the license plate of the vehicle. Application has been tested on 15 samples of data plate number of vehicles with standard specifications of the Police of the Republic of Indonesia. Tests of 15 data samples were performed 5 times using several variations of the ratio values ​​of the threshold. From the results of the overall testing that has been done, the average level of accuracy in the use of bounding box is 54% in the whole test. In the use of selective ratio bounding box, the highest average accuracy level in the second test was 92% and the lowest accuracy level in the 4th test was 68%. While on the other test obtained the same average accuracy that is equal to 88%.